Efisiensi Usahatani Padi Aromatik dan Sapi Potong pada Lahan Sawah Tadah Hujan Dengan Sistem Integrasi di Kabupaten Seluma Provinsi Bengkulu - Yesmawati, Yesmawati; Kusnadi, Harwi; Mikasari, Wilda; Robiyanto, Robiyanto (Seminar Nasional Lahan Suboptimal, 2018)
Yesmawati et al, 2019. Efficiency of Aromatic Rice and Coconut Rice use on Rain Wood Land With Integration System in District Seluma Province Bengkulu. pp. 510-518. Integrated farming of rainfed lowland rice and beef cattle is an effort that combines rice cultivation in rainfed lowland and beef cattle fattening. Rainfed rice fields can produce straw which can be used as animal feed and beef cattle can provide cow dung as an organic fertilizer needed in rainfed lowland rice farming. Integration between rice farming in rainfed lowland and fattening beef cattle is expected to create minimal production costs and utilization of local resource potential. This study was conducted to determine the financing structure and integration of aromatic rice and beef cattle in Seluma Regency, Bengkulu Province. The assessment method used is survey method. Primary data collection was carried out by direct observation and interviews with 25 respondents. The results of the study showed that the integration of aromatic rice paddies carried out on rainfed lowland rice and beef cattle was able to significantly increase farmer income by 1,811,667 / month and rice farmers income by Rp. 1,330,000 / month.